PENYULUHAN PENCEGAHAN CACINGAN PADA MASYARAKAT DI DESA SUNGAI KUNYIT HULU, KABUPATEN MEMPAWAH - Abdurraafi' Maududi Dermawan; Fath Dwisari; Fitri Khotimatus Sa'adah; Tri Utari (Politeknik 'Aisyiyah Pontianak, 2023)
Worm infection is a disease caused by the transmission of Soil Transmitted Helminth (STH) parasites. Currently, deworming control, especially in rural communities, which involves government control and local health centers in tackling worm infections, is limited. Therefore, strategies are needed to control worm infections. The actions that can be taken to prevent worm infections are promotive and preventive. One of these strategies is realized through the implementation of promotive and preventive measures. The education was conducted on October 13, 2022. The number of participants who attended the counseling was 19 people consisting of Posyandu volunteers and residents of Sungai Kunyit Hulu Village. Based on the results of the questionnaire, an average of 86.32% of participants already knew about worms, symptoms, and characteristics of worms in children, causes, and ways to prevent worms. In addition, the post-test results showed that 94.7% of participants were able to answer correctly questions related to the causes of worms, 100% of participants were able to answer correctly about the characteristics of children infected with worms, 89.47% of participants answered correctly how to prevent worms and 100% of participants answered correctly the actions that must be taken if symptoms of worms are found.